MENINGKATKAN KETERAMPILAN MEMBACA AL-QUR’AN MELALUI METODE TALAQQI PADA AYAT 190-191 DAN 159 Q.S. ALI IMRAN. - Farikhah Farikhah (Atthiflah: Journal of Early Childhood Islamic Education, 2021)
As Muslims we have an obligation to pay attention to the Qur'an, namely by always reading it, memorizing it or interpreting it. Allah (SWT) has promised the preservationists of His book in the form of reward, raised and given happiness both in the world and in the Hereafter. The problem that I found when teaching online (online) on the material aspects of the Qur'an, it turns out that many students who collect the bill of reading QS assignments. Ali Imran verses 190-191 and 159 many reading errors. Therefore, it can be found that the methods used previously do not improve the ability to read the Qur'an in accordance with the rules of the law of reading or tajwid. Then it is necessary to apply some alternative solutions that are needed, namely: the right method that can improve the skills of reading the Qur'an according to tajwid rules and media that can facilitate improving the skills of reading the Qur'an according to tajwid rules. The talaqqi method makes it easier for researchers to choose the right way to convey knowledge, because of the direct interaction between teachers and students, making it easier for teachers to recognize students' personalities and abilities by using zoomeeting applications. In this study the method used is Class Action Research. The essence of the nature carried out in classroom action research (PTK) is in the framework of teachers willing to introspect, reflect, reflect or evaluate themselves so that their abilities as a teacher / teacher are expected to be quite professional. Based on the results of research it can be concluded that through the talaqqi method can improve the ability to read the Qur'an of students. This can be seen in each cycle, in the pre-cycle the average results of students' Qur'anic reading ability by 65% with incomplete categories, and only 8 students out of 23 students only reached the average grade (completed). After the first cycle, the ability to read the Qur'an rose to 85% which was categorized as complete which amounted to 17 students out of 20 students. In cycle II the ability to read the Qur'an students experienced a significant increase with an average score of 80.5 with a complete category, with the number of students completed as many as 20 students.